Ten years disseminating and promoting science, RPCC-UACJS: a brief history of the development of a journal - Carro Pérez, Ennio Héctor (Universidad Autónoma de Tamaulipas, 2019)
The history of the Journal of Psychology and Behavioral Sciences of the Academic Unit of Legal and Social Sciences, started in 2009, has been crossed by moments of uncertainty and enthusiasm, frustrations and high expectations. Despite being born in an unfortunate environment, austere in the collection of contributions, the ten-year project looks vigorous and with a happy horizon. The present text tries to offer a synthesis of what has been an editorial project dedicated to the dissemination and scientific promotion in the study of human behavior. Ten years after its existence, the project continues in force.